Useful clinical findings and simple laboratory data for the diagnosis of seasonal influenza - Takeoka, Hiroaki; Horibata, Ken; Hiyoshi, Tetsuya; Noge, Ikuma; Sakihara, Eishi; Sechi, Yusuke; Okutsu, Shota; Suzuyama, Hiroki; Nabeshima, Shigeki (Journal of General and Family Medicine, 2021)
Background When using rapid antigen test kits for the diagnosis of influenza, false‐negative results may occur if done too soon after the onset of symptoms. The purpose of this study was done to determine clinical laboratory items other than rapid antigen testing are useful for diagnosing influenza. Methods The subjects were 915 patients who visited the outpatient clinic of hospital between April 2010 and March 2017 during the influenza epidemic seasons, from December to April, and had both fever of 37.0 degrees or more and cold symptoms. Results Of the 214 patients who met the inclusion criteria, 176 had influenza. Multivariate analysis extracted patient consultation within four days of onset, fever of 37 degrees or higher, posterior pharyngeal lymphoid follicles, CRP of 0.77 mg/dL or less, and a lymphocyte count of 900/μL less as independent variables. Conclusion In previous study, lymphoid follicles on the posterior pharyngeal wall and decreased lymphocyte count were reported as influenza‐specific findings. Both were confirmed with high specificity in our study, indicating that both would be useful when patients with influenza‐like symptoms were false‐negative for the rapid antigen test. The influenza follicles are aggregated in the part of the posterior pharyngeal wall.